Phytoremediation of soils contaminated by leachate in landfills with andean forest species - Carrillo-Aparicio, Diego (2025)
Solid waste management worldwide is insufficient, storage activities generate leachates that can negatively affect soil physical and chemical properties. The efficiency of Salix humboldtiana, Alnus acuminata, Lafoensia acuminata, Leucaena leucocephala and Sambucus nigra species as phytoremediation alternatives in soils contaminated by leachates was evaluated. Two initial analyses were carried out to determine the physicochemical properties of uncontaminated and leachate-contaminated soil. Subsequently, five individuals of each species were established in the two treatments (contaminated and non-contaminated soil) to compare their development and growth. Then, the accumulation of elements in the seedlings was quantified by foliar analysis and, through a final soil analysis, the degree of phytoremediation of the soil by the different species was evaluated. The species located in the contaminated soil showed less growth and development in four of the five variables studied. Leucaena leucocephala showed better performance by absorbing a higher concentration of iron in its leaves, while Salix humboldtiana absorbed a higher concentration of zinc and sulfur. The contaminated soil from the phytoremediation treatment showed a lower concentration of most of the elements. Contaminated soils have a negative influence on the growth of height, diameter, crown diameter, root depth and the number of leaves on forest species. Finally, the greater root growth in contaminated soils is of the species Alnus acuminata and a greater height in Salix humboldtiana, make them suitable in soil phytoremediation processes.